Dizeres sobre e na sala de aula: aspectos da constituição do professor de LE a partir da relação entre teoria e prática - Araújo, Nélio Martins (2015)
This thesis aims at analyzing aspects of the foreign language teacher\'s constitution to what concerns the relationship between theory and practice. The main goal of this work is to enlarge the dialogue between theory and practice in the context of the language teaching and learning. The specific goals are: (i) To verify the regularities in teachers\' utterances enunciated in the classroom, identifying marks of interdiscursivity among theories on the teaching and the learning process of foreign languages; (ii) To identify and to analyze the incidence of traits of the teacher\'s theoretical formation, recovered from the analyzed utterances about the foreign language teacher\'s constitution; (iii) To discuss the relation between the formation received by the teacher and the foreign language teachers constitution. The hypothesis that guides this research considers that far away from establishing a simple tension between theory and practice, what is realized in the teachers performance, given the contingency of a classroom, is the traits of the subjectivity that the teachers established during their constitution as teachers with the theoretical knowledge and with the experience with the language learning and teaching. That contingency, in the teaching and learning process, mobilizes, or not, through discursive memory, something of the teachers theoretical-practical formation resulting from their subjective investment on the language teaching and learning. It is certain that such a process affects their constitution as teachers. In order to compose the corpus of the research, classes given by two English teachers from the sixth grade of elementary public schools were recorded. Interviews with these same teachers were also collected. Theoretically, this research is founded on concepts of Discourse Analysis that assumes the subject being constituted by the flaw, for the non possibility to say everything; marked by the contradiction and obstructed by the real of the language. Thus, it was assumed that the teachers constitution, given their relation to the teaching and learning process, can suffer displacements that result from discursive crossings that (re)constitute their relation to the knowledge production in the classroom. Three discursive crossings were noticed constituting the teachers from the subjective processes promoted and suffered by them. The first comes from the academic formation, in the form of traits of theories with which they maintained contact. The second results from their experiences with the language teaching and learning process. Finally, other discursive crossing was an imaginary that seemed to constitute the teachers, under which they showed they did not believe the possibility of teaching and learning a foreign language within public schools. Results have shown that a discursive vision of the teachers and of their relationship to the theory and the practice of foreign language teaching can represent a base for any kind of the (trans)formation wanted in the process of teaching and learning a foreign language at public schools.